2013
DOI: 10.1371/journal.pone.0084430
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Mucus Thickness and Ion Secretion during Citrobacter rodentium Infection and Clearance

Abstract: Citrobacter rodentium is an attaching and effacing pathogen used as a murine model for enteropathogenic Escherichia coli. The mucus layers are a complex matrix of molecules, and mucus swelling, hydration and permeability are affected by many factors, including ion composition. Here, we used the C. rodentium model to investigate mucus dynamics during infection. By measuring the mucus layer thickness in tissue explants during infection, we demonstrated that the thickness changes dynamically during the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
59
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 51 publications
6
59
1
Order By: Relevance
“…Fluorescence microscopy of the pig colon tissue revealed that the mucus layer in the healthy pig colon, including in the colon of the inoculated pigs that did not develop SD, was organized in striations parallel to the mucosa and consisted mainly of the MUC2 mucin (Fig. 1A to C), similarly to the mucus structure reported for the mouse colon (2,27). In contrast, during infection with B. hyodysenteriae, a massive increase in MUC2 levels and de novo production of MUC5AC was observed in the four inoculated pigs with severe clinical signs of dysentery ( Fig.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Fluorescence microscopy of the pig colon tissue revealed that the mucus layer in the healthy pig colon, including in the colon of the inoculated pigs that did not develop SD, was organized in striations parallel to the mucosa and consisted mainly of the MUC2 mucin (Fig. 1A to C), similarly to the mucus structure reported for the mouse colon (2,27). In contrast, during infection with B. hyodysenteriae, a massive increase in MUC2 levels and de novo production of MUC5AC was observed in the four inoculated pigs with severe clinical signs of dysentery ( Fig.…”
Section: Resultssupporting
confidence: 69%
“…The antibodies used have previously been shown to detect their specific targets in humans and mice (27,28), but no MUC2 or MUC5AC antibodies have been verified for use in pigs. To be certain that the stain represented MUC5AC and MUC2, we confirmed that the antibodies we used for the immunofluorescence indeed bound to the isolated mucins in specific manners that differed between the antibodies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Storage droplets or vesicles continuously adjust their size, shape and contents through ongoing exchange with the surroundings, creating intrinsically responsive control mechanisms that tie secretion to a wide range of chemical and physical stimuli and feedback signals. [10][11][12][13] At the same time, collective changes in the stores are reported to the organism, alerting it that it needs to drink or eat to replenish the limited supply. Many synthetic approaches have been developed to enable triggered release from microcapsules, hydrogels, nanoparticles, vesicles, micelles, mesoporous carriers and other containers.…”
mentioning
confidence: 99%